Model Pembelajaran Kolaboratif Berbasis Keterampilan Interpersonal untuk Meningkatkan Kesantunan Tindak Tutur Mahasiswa PBSI - Fitriani Fitriani; Arni Arni; Lelita Ayu Rahmawati (Universitas PGRI Pontianak, 2025)
This study aims to describe the course profile of the Pragmatics subject, specifically on speech act politeness, and to identify learning obstacles experienced by Indonesian Language and Literature Education (PBSI) students at UPGRI Pontianak. A mixed-methods approach was employed, integrating qualitative and quantitative techniques. Data were collected through classroom observations, semi-structured interviews, enrichment book evaluation sheets, and student response questionnaires. Qualitative data from observations, interviews, and expert and student feedback were analyzed thematically, while the feasibility of the enrichment book was examined using descriptive statistics based on average validation and trial scores. The findings indicate that the Pragmatics course emphasizes students’ competencies in understanding and applying speech act politeness across academic, social, and digital contexts. However, several obstacles were identified, including the abstract nature of pragmatic theories, cultural variability in politeness interpretation, limited exposure to authentic discourse analysis, the influence of digital and colloquial language, mother tongue interference, and insufficient practice supported by contextual and local examples.